Fibronectin Adsorption to Nanopatterned Silicon Surfaces. (6th February 2008) - Salakhutdinov, I.; VandeVord, P.; Palyvoda, O.; Matthew, H.; Tatagiri, G.; Handa, H.; Mao, G.; Auner, G. W.; Newaz, G.
Abstract : The possibility of using surface topography for guidance of different biological molecules and cells is a relevant topic that can be applied to a wide research activity. This study investigated the adsorption of fibronectin to a diffraction grated silicon surface. The rectangular grating profile featured a controlled surface with 350 nm period and a corrugation depth of 90 nm. Results demonstrated that the controlled surface had a significantly positive effect on the fibronectin binding. Thus, nanoscale surface topography can enhance fibronectin binding.